Recent advances in gene therapy for thalassemia - J V Raja; M A Rachchh; R H Gokani (Wolters Kluwer Medknow Publications, 2012)
Thalassemias are genetically transmitted disorders. Depending upon whether the genetic defects or deletion lies in transmission of α or β globin chain gene, thalassemias are classified into α and β-thalassemias. Thus, thalassemias could be cured by introducing or correcting a gene into the hematopoietic compartment or a single stem cell. Initial attempts at gene transfer have proved unsuccessful due to limitations of available gene transfer vectors. The present review described the newer approaches to overcome these limitations, includes the introduction of lentiviral vectors. New approaches have also focused on targeting the specific mutation in the globin genes, correcting the DNA sequence or manipulating the development in DNA translocation and splicing to restore globin chain synthesis. This review mainly discusses the gene therapy strategies for the thalassemias, including the use of lentiviral vectors, generation of induced pluripotent stem (iPS) cells, gene targeting, splice-switching and stop codon readthrough.